2007
DOI: 10.1139/e06-107
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic evolution of the Yaoundé segment of the Neoproterozoic Central African Orogenic Belt in southern Cameroon

Abstract: The deformation history of the Neoproterozoic Central African Orogenic Belt in southern Cameroon is well recorded in the low- to high-grade rocks outcropping in the area around Yaoundé. The fabrics in these rocks are consistent with two main ductile deformation events D1 and D2. D1 predated emplacement of calc-alkaline dioritic bodies and caused the formation of nappes that resulted in high-pressure granulite metamorphism of soft sediments. A strong overprinting of these nappes during D2 symmetric extension, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 30 publications
3
73
0
2
Order By: Relevance
“…Geophysical studies [7] [10] [23] show that the boundary of CC and Pan-African is around 4˚N. The tectonic features (faults and folds) are fitted into the CAFB's deformation history and could be due to the Tran Saharan east-west collision system [24]. Some buried faults have being confirmed in the geophysical studies [11] [23] [25].…”
Section: Geology and Tectonic Settingmentioning
confidence: 83%
“…Geophysical studies [7] [10] [23] show that the boundary of CC and Pan-African is around 4˚N. The tectonic features (faults and folds) are fitted into the CAFB's deformation history and could be due to the Tran Saharan east-west collision system [24]. Some buried faults have being confirmed in the geophysical studies [11] [23] [25].…”
Section: Geology and Tectonic Settingmentioning
confidence: 83%
“…The S 2 foliation is a regional, steeply dipping planar fabric with variably oriented stretching lineation and large-scale open folds that are associated with N-S trending sinistral and dextral strike-slip faults and mylonitic (S 3 ) foliation. The S 2 foliation is well observed in the greenstone units of the Ntem complex and its development is linked to dome-and-basin tectonics related to diapiric movements [18].…”
Section: Introductionmentioning
confidence: 95%
“…Also, [7] showed the morphological difference and the tectonically subdivision into two tectonic sectors corresponding to the Congo Craton in the south, Pan-African in the north and helped identify the tectonic boundary separating them at depth. The tectonic features (faults and folds) are fitted into the CAFB's deformation history and could be due to the Trans-Saharan east-west collision system [18]. Some buried faults have been confirmed in geophysical studies [16] [19].…”
Section: Introductionmentioning
confidence: 99%
“…P-T conditions range from 4-9 kbar/675-575°C in the Mbalmayo schists to 7-12 kbar/ 800°-550°C in the Yaoundé migmatites (Mvondo et al, 2003). An alternative interpretation of the exhumation of HP-HT granulites in the Yaoundé Group suggests it is linked with late PanAfrican extensional evolution (Mvondo et al 2003(Mvondo et al , 2007; this interpretation is neither compatible with the important crust thickness (38-42 km) in the Yaoundé region (Poudjoum Djomani et al, 1995), nor with the Adamawa Tertiary uplift situated far to the north as suggested by the authors. The Rocher du Loup shear zone (RLSZ, Fig.…”
Section: Fig 3 Fold Generations and Geometry In Northern Cameroon (mentioning
confidence: 99%